Efforts to Improve Speaking Skills through Storytelling Methods Assisted by Hand Puppets for Students at RA Taqiyya Kartasura Sukoharjo - Kandari, Hindun Hatsmah; Listiyani, Ida (Jurnal Profesi Guru Indonesia, 2025)
Efforts to Improve Speaking Skills Through Storytelling Methods with Hand Puppet Media for Zaid/A1 Class Students at RA Taqiyya Kartasura in the 2020/2021 Academic Year. This study aims to improve speaking skills through storytelling methods with hand puppet media for Zaid/Group A1 students at RA Taqiyya Kartasura. Speaking skills are one of the important aspects in early childhood development, because through speaking children can communicate and interact with others, besides speaking is one of the provisions for children in socializing with the surrounding environment. The subjects of this study were Zaid/A1 class students at RA Taqiyya Kartasura, totaling 24 children consisting of 13 boys and 11 girls. The activity took place on Monday-Friday. Based on the research simulation carried out, hand puppet media can be an alternative to improve speaking skills in children aged 4-5 years, because hand puppets are one of the media that are interesting for children and very easy to use. In addition, the teacher's readiness in preparing supporting media such as puppet stages and the teacher's delivery method in telling stories also needs to be considered so that children are more interested in paying attention and are willing to try telling stories with hand puppets and ultimately efforts to improve speaking skills through the storytelling method with hand puppet media are successful.